MIXED FINITE ELEMENT FORMULATION OF THE BIHARMONIC EQUATION - GARNADI, A. D. (School of Data Science, Mathematics and Informatics, IPB University, 2005)
We will provide an abstract setting for mixed ﬁnite element method for biharmonic equation. The abstract setting casts mixed ﬁnite element method for ﬁrst biharmonic equation and sec- ond biharmonic equation into a single framework altogether. We provide error estimates for both type biharmonic equation, and for the ﬁrst time an error estimate for the second biharmonic equation.